2012
DOI: 10.5402/2012/456762
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Electronic Properties of Pure Ta, TaNO, and TaZrNO with Ab Initio Calculations

Abstract: This paper presents the results of self-consistent first-principle calculations for the crystal structure and electronic structure of pure tantalum, TaNO, and TaZrNO within density functional theory (DFT) for the sake of comparison and shows the influence of allowing elements on the interatomic distance and the Fermi level. The large total densities of states (TDOS) value for TaZrNO implies the highest electronic conductivity. The difference in values is due to the Zr metallic atoms presence in TaZrNO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In 2011, Chen and Wang 247 performed DFT calculations to investigate the phase stability, the formation of intrinsic defects and their inuences on the electronic conductivity of TaON and found that stoichiometric TaON is observed to be stable under relatively O poor conditions and can be easily oxidized due to the easy formation of O N antisites; however, with the deep donor states associated with the O and N vacancies, the donor state of the O N antisite is shallow and has a delocalized distribution, indicating a better electronic conductivity in TaON compared to Ta 2 O 5 and Ta 3 N 5 . In 2012, Chihi et al 248 performed ab initio calculations to investigate the structural and electronic properties of pure Ta, TaON, and ZrTaON. The authors found that the large total density of states for ZrTaON implies the highest electronic conductivity.…”
Section: Tantalum Oxynitride (Taon)mentioning
confidence: 99%
“…In 2011, Chen and Wang 247 performed DFT calculations to investigate the phase stability, the formation of intrinsic defects and their inuences on the electronic conductivity of TaON and found that stoichiometric TaON is observed to be stable under relatively O poor conditions and can be easily oxidized due to the easy formation of O N antisites; however, with the deep donor states associated with the O and N vacancies, the donor state of the O N antisite is shallow and has a delocalized distribution, indicating a better electronic conductivity in TaON compared to Ta 2 O 5 and Ta 3 N 5 . In 2012, Chihi et al 248 performed ab initio calculations to investigate the structural and electronic properties of pure Ta, TaON, and ZrTaON. The authors found that the large total density of states for ZrTaON implies the highest electronic conductivity.…”
Section: Tantalum Oxynitride (Taon)mentioning
confidence: 99%
“…Thus, it is necessary to investigate the underlying electronic structure of β-Ta to determine the origin of the property envelope demonstrated by the b-phase and the differences from a-Ta. For b-Ta, studies of the electronic structure by X-ray photoelectron spectroscopy (XPS) measurements including valence band and theoretical density of states (DOS) with density functional theory (DFT) calculations are scarce, and solely for the b-uranium structure [19].…”
Section: Introductionmentioning
confidence: 99%